Matéria orgânica e qualidade do solo em pastagem submetida a adubação com cama de aviário no Cerrado - Silva, Camila Menezes Rodrigues da (2017)
The objective of the present study was to evaluate the accumulation of organic matter and the biological attributes of soil quality in pasture submitted to fertilization with aviary beds. The soil of the experimental area is a Distroferric Red Latosol divided into 16 paddocks of 0.5 ha each with Uroclhoa decumbens grass in a rotational grazing system. The experiment consists of the following accumulated doses of turkey bed and the respective years of application: T0 - control without application; T1 - 26.32 Mg ha 1 (8.70 - 2008 + 7.32 - 2011 + 5.30 - 2012 + 5.00 - 2014); T2 - 43.15 Mg ha-1 (7.81 - 2008 + 8.69 - 2010 + 7.89 - 2011 + 7.34 - 2012 + 5.71 - 2013 + 5.71 - 2014); 3 - 57.6 Mg ha-1 (14,45 - 2008 + 7,81 - 2009 + 8,69 - 2010 + 7,89 - 2011 + 7,34 - 2012 + 5,71 - 2013 + 5,71 - 2014). There were increases in the contents and stocks of total organic carbon, total nitrogen and particulate as a function of turkey bed application. Differently, the particulate organic carbon was not influenced by the treatments. The high N availability, provided by the fertilizer, reduced the COP / NP ratio, but did not influence the COT / NT ratio. The microbial biomass was modified before the doses, reaching maximum points for the C-BM, metabolic and microbial quotient in T2. From the second dose, there were higher C and N rent rates for the 0-1m layer compared to the 0-0.2m layer. The attributes that most contributed to soil quality monitoring were C-BM, the microbial quotient, the metabolic quotient and the POP. The sequential application of increasing doses of turkey litter was efficient in promoting improvements in the chemical and biochemical attributes of the soil, with the increase of the stocks and contents of soil C and N and modification of the microbial biomass. Evaluations of retention rates of organic matter in the 0-0.2 m layer underestimate the results in relation to the 0.0-1.0 m layer. The attributes that contributed most to the soil quality in this management system were: microbial biomass carbon, microbial and metabolic quotient, particulate organic carbon. The application of turkey litter promoted increases in soil carbon and nitrogen contents and also positively influenced the activity of microbial biomass. It increased the retention rate of carbon and nitrogen along the soil profile. The microbiological attributes contributed the most to the improvement of soil quality.